2020
DOI: 10.1111/1750-3841.15342
|View full text |Cite
|
Sign up to set email alerts
|

Use of potassium polyaspartate for stabilization of potassium bitartrate in wines: influence on colloidal stability and interactions with other additives and enological practices

Abstract: The research was aimed at verifying the efficacy of potassium polyaspartate (KPA), added at bottling, for prevention of the precipitation of potassium bitartrate (KHT). The stability of KHT was determined with the mini‐contact test and the cold test. The effect of KPA on the colloidal stability of white and red wines was also studied. Turbidity, color, and total anthocyanins and flavonoids (red wines only) were monitored. In the first experiment, the stabilizing effect of KPA added at bottling, with or without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…Several studies have shown that CMC, even without the aid of GA, can be a KHT crystallization inhibitor suitable for red wines [ 19 , 20 , 37 , 38 ]; however, the efficiency of this additive for tartaric stabilization depends on the chemical composition of the wine as well as doses [ 39 ], and our results showed how in 2016 the wines treated with CMC+GA remained stable after one year in the bottle but the same result was not observed in 2017, even though the tartaric acid, Ca and K concentration ( Table 1 and Table 2 ) were lower in this wine. The inhibitory effect of KPA+GA remained after one year in the wine and similar results were observed by Canuti et al [ 40 ] with KPA and Bosso et al [ 36 ] working with KPA combined with GA.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Several studies have shown that CMC, even without the aid of GA, can be a KHT crystallization inhibitor suitable for red wines [ 19 , 20 , 37 , 38 ]; however, the efficiency of this additive for tartaric stabilization depends on the chemical composition of the wine as well as doses [ 39 ], and our results showed how in 2016 the wines treated with CMC+GA remained stable after one year in the bottle but the same result was not observed in 2017, even though the tartaric acid, Ca and K concentration ( Table 1 and Table 2 ) were lower in this wine. The inhibitory effect of KPA+GA remained after one year in the wine and similar results were observed by Canuti et al [ 40 ] with KPA and Bosso et al [ 36 ] working with KPA combined with GA.…”
Section: Resultssupporting
confidence: 87%
“…Several studies have shown that CMC, even without the aid of GA, can be a KHT crystallization inhibitor suitable for red wines [19,20,37,38]; however, the efficiency of this additive for tartaric stabilization depends on the chemical composition of the wine as well as doses [39], and our results showed how in 2016 the wines treated with CMC+GA remained stable after one year in the bottle but the same result was not observed in 2017, even though the tartaric acid, Ca and K concentration (Tables 1 and 2) were lower in this wine. The inhibitory effect of KPA+GA remained after one year in the wine and similar results were observed by Canuti et al [40] with KPA and Bosso et al [36] working with KPA combined with GA. All treatments stabilized the wine, especially the cold treatment, and the wine maintained its stability after a year in the bottle. When looking at the two subtractive methods, the one that led to the most stable wine was ED, although after a year, the wine treated with IER showed the lowest values in the stability test (highest stability).…”
Section: Tartaric Stability Testsupporting
confidence: 86%
See 2 more Smart Citations
“…The purpose of stabilization is to ensure the clarity of the wine during aging and storage. Stabilization is carried out by removal (adsorption) of polyphenolic, protein and crystalline compounds with gluing agents, as well as filtration using membranes [1][2][3][4]. Traditionally, these are bentonite of various modifications, fish glue, albumin, chitosan (and others) and polymer compounds -PVP, PAA, and POE in combinations required for a specific stabilization method [5].…”
Section: Introductionmentioning
confidence: 99%